1991
DOI: 10.1113/jphysiol.1991.sp018482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low ionic strength media on passive human red cell monovalent cation transport.

Abstract: SUMMARY1. The effect of low ionic strength media on the residual, i.e. (ouabain + bumetanide+ Ca2+)-insensitive, K+ influx was characterized in human red blood cells.2. This K+ flux was enhanced significantly in isotonic solutions of low ionic strength using sucrose to maintain constant osmolarity. This effect was found for fresh red blood cells as well as for stored (bank) red blood cells. However, the absolute magnitude of K+ influx in solutions of low ionic strength was halved for stored red blood cells.3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 41 publications
3
48
1
Order By: Relevance
“…Characterization of the K + influx via KCC and KNHE in the CHC patient's erythrocytes showed that the unusually high cation permeability in these cells at low temperature is, at least in part, a cumulative effect of an abnormal activation of two independent ion transport systems: KCC and KNHE. As follows from the Table 1, and in agreement with former reports, 22,30 both ion transporters are almost silent in RBC from healthy donors (and the patient's family members), particularly during cold storage. Several lines of evidence point towards an abnormally high activity of the cation-proton exchanger in RBC of the CHC patient at 37°C and even more so at 0°C.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Characterization of the K + influx via KCC and KNHE in the CHC patient's erythrocytes showed that the unusually high cation permeability in these cells at low temperature is, at least in part, a cumulative effect of an abnormal activation of two independent ion transport systems: KCC and KNHE. As follows from the Table 1, and in agreement with former reports, 22,30 both ion transporters are almost silent in RBC from healthy donors (and the patient's family members), particularly during cold storage. Several lines of evidence point towards an abnormally high activity of the cation-proton exchanger in RBC of the CHC patient at 37°C and even more so at 0°C.…”
Section: Discussionsupporting
confidence: 91%
“…A minor increase in residual K + leak at low temperature had already been reported and was especially pronounced under conditions of low ionic strength. 22,31 This cold-induced response attributed to the activation of the KNHE 16 is amplified many fold in the patient's RBC. When the patient's RBC were suspended in cold, NaCl-containing solution, they showed minor changes in cell volume/density ( Figure 1B) because the Na + accumulation almost matched the K + loss ( Figure 2B and C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incubating human red blood cells in low ionic strength media induces a transport pathway selective for monovalent cations (Na+, K+), but not Ca2" or lysine (Bernhardt et al 1991), which shows properties reminiscent of the volume-activated organic substrate transport pathway in fish erythrocytes (Kirk et al 1992) and malariainfected human erythrocytes . To investigate the characteristics of the low ionic strengthinduced pathway further we have compared taurine transport in human red cells incubated in a buffered sucrose medium (LIS) with cells in Mops-buffered physiological saline.…”
Section: Germanymentioning
confidence: 99%